Food and nutrition security in the process of globalization and urbanization - Kracht, Uwe (Spektrum, 2005)
The reader in two volumes examines key issues of food and nutrition security under the driving forces of globalization and urbanization. The different sections and chapters present approaches to food security throughout the world in a historic as well as a systematic perspective. The methods applied are both qualitative and quantitative (two econometric models and one cluster analysis). Although much has been written on food security, a systematic treatment of a historical-empirical and theoretical-analytical view is a recent development, and we have therefore chosen a'holistic'approach. The first volume contains contributions of a more historical-empirical nature; the second volume is policy oriented. Each volume is essentially self-contained and can be read in its own right, according to the reader's interest. The current work builds on our 1999 volume on"Food Security and Nutrition - The Global Challenge". Our new reader comprises 62 articles by 71 authors. It is written for a broad audience, including scientists, experts, consultants, practitioners of development aid and students. The reader constitutes one of the most comprehensive compendia of its kind.